Photoluminescent low-haze surface treatment film and preparation method thereof

The photoluminescent low haze surface treatment film prepared by using the hydrothermal method of Ce3+ and Tb3+ co-doped CaF2 phosphor and SiO2 adsorption leveling agent on the liquid crystal display screen, the problems of laser point spot clarity and display screen clarity are solved, and a higher display effect is achieved.

CN119505327APending Publication Date: 2025-02-25HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411834714.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve clear laser point spots on liquid crystal display screens without affecting the clarity of the display screen, and the display backlight will interfere with the detection of laser light.

Method used

The CaF2 phosphor co-doped Ce3+ and Tb3+ was synthesized by hydrothermal method, and SiO2 adsorption leveling agent was introduced to its surface layer to prepare a photoluminescent low haze surface treatment film and coated into a transparent film.

Benefits of technology

It improves the clarity and gloss of the display screen, enhances the visibility of the laser spot, and solves the problems of dim spots of laser pointers and backlight interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505327A_ABST
    Figure CN119505327A_ABST
Patent Text Reader

Abstract

The photoluminescence low-haze surface treatment film comprises a transparent support body and a hardened coating coated on the surface of the transparent support body, the hardened coating is formed by coating the surface of the transparent support body with a coating liquid, drying the coating liquid in a drying oven and curing the coating liquid with ultraviolet light, and the coating liquid comprises the following substances in parts by weight: 30-40 parts of polyurethane acrylic resin; 46.5 to 66.4 parts of an organic solvent; 0.1 to 0.5 part of a SiO2 adsorption leveling agent; 0.5 to 5 parts of a photoinitiator; and 3-8 parts of CaF2 fluorescent powder co-doped with Ce < 3 + > and Tb < 3 + >. The CaF2 fluorescent powder co-doped with Ce < 3 + > and Tb < 3 + > is synthesized through a typical hydrothermal method, the leveling agent containing SiO2 is introduced into the surface layer of the fluorescent powder, the prepared coating liquid is coated into a transparent film, the problem that light spots of a laser pen in a display panel are dark is solved, and meanwhile the definition of a display screen is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photoluminescent low-fog surface treatment film and a preparation method thereof, belonging to the technical field of transparent films. Background Art

[0002] In recent years, the LCD industry has developed rapidly in the field of optoelectronic display, and production capacity has expanded rapidly. From the perspective of the market demand for optoelectronic display applications, the compound growth rate of LCD panels from 2016 to 2025 will reach 4%. At the same time, as the size of LCD screens increases, more and more panel displays are used in presentations, and presentations can be presented directly in flat-panel displays. Flat-panel displays can provide higher clarity and brighter color contrast than beam projection systems consisting of beam projectors and white screens. However, it is difficult for flat-panel displays to clearly display specific content on the screen using a laser pen. In addition, the display is self-luminous, and the strong light from the display backlight will interrupt the detection of the laser. Roughening the surface treatment film of the display is a way to improve the visibility of the laser spot, but this method will deteriorate the clarity of the display. Summary of the invention

[0003] The present invention is to overcome the disadvantages of the prior art and provide a photoluminescent low haze surface treatment film and a preparation method thereof. Ce is synthesized by a typical hydrothermal method. 3+ and Tb 3+ The co-doped CaF2 phosphor has a leveling agent containing SiO2 introduced into the surface layer of the phosphor, and the prepared coating liquid is applied to a transparent film, which solves the problem of dim light spots of the laser pen in the display panel and improves the clarity of the display screen.

[0004] The technical solution adopted by the present invention to solve its technical problem is:

[0005] A photoluminescent low-haze surface treatment film, the treatment film comprises a transparent support and a hardened coating coated on the surface of the transparent support, the hardened coating is formed by coating a coating liquid on the surface of the transparent support, drying in an oven, and curing with ultraviolet light, the coating liquid comprises the following substances:

[0006]

[0007]

[0008] Ce 3+ and Tb 3+ 3 to 8 parts of co-doped CaF2 phosphor.

[0009] The above-mentioned photoluminescent low-haze surface treatment film, the Ce 3+ and Tb 3+ The particle size of the co-doped CaF2 phosphor is 500-700nm.

[0010] In the above-mentioned photoluminescent low-haze surface treatment film, the SiO2 adsorption leveling agent is any one of polyacrylate, silicone resin and fluorine surfactant.

[0011] The above-mentioned photoluminescent low-haze surface treatment film, the Ce 3+ and Tb 3+ The mass ratio of the co-doped CaF2 phosphor to the SiO2 adsorption leveling agent is 1:(0.03-0.08).

[0012] In the above-mentioned photoluminescent low-haze surface treatment film, the organic solvent is any one of isopropyl alcohol, ethyl acetate, and butyl acetate, or a mixture of any two thereof; and the photoinitiator is TPO.

[0013] The above-mentioned photoluminescent low-haze surface treatment film, the transparent support is a triacetyl cellulose film, a polyester film, a PMMA film, a SRF film, the thickness of which is 50 μm to 125 μm, wherein the coating thickness is 3-5 μm.

[0014] A method for preparing a photoluminescent low-haze surface treatment film, the preparation method comprising the following steps:

[0015] a. Preparation of Ce by hydrothermal synthesis 3+ and Tb 3+ Co-doped CaF2 phosphor;

[0016] b. Prepare Ce 3+ and Tb 3+ The co-doped CaF2 phosphor is added to a certain amount of solvent and dispersed into single-particle nanoparticles by high-speed stirring;

[0017] c. Adding part of SiO2 adsorbing leveling agent to the uniformly mixed single-particle nanoparticles to obtain nanoparticle pre-solution A;

[0018] d. Mix and dilute the formulated amount of polyurethane acrylic resin with a certain amount of solvent, add another part of SiO2 adsorption leveling agent after mixing, and stir at a low speed to obtain resin dilution B;

[0019] e. Add the nanoparticle pre-solution A to the resin diluent B, and add a formulated amount of photoinitiator, and stir at high speed to obtain a coating solution;

[0020] f. The coating liquid is coated onto a transparent support by a wire rod, dried at 85° C., and then UV cured to obtain the photoluminescent low-haze surface treatment film.

[0021] The method for preparing the above-mentioned photoluminescent low-haze surface treatment film, in the step a, the hydrothermal synthesis method is used to prepare Ce 3+and Tb 3+ The co-doped CaF2 phosphor comprises the following steps:

[0022] Step 1: Dissolve calcium nitrate (Ca(NO3)2·6H2O), cerium nitrate (Ce(NO3)3·6H2O), terbium nitrate (Tb(NO3)3·5H2O) and disodium ethylenediaminetetraacetic acid (Na2EDTA) in deionized water and stir for 20 min using a high-speed stirrer at a speed of 1000 rpm / min;

[0023] Step 2: Use ammonia water to adjust the pH of the solution in step 1 to 6-7;

[0024] Step 3: dissolving sodium fluoroborate (NaBF4) to prepare a sodium fluoroborate (NaBF4) solution;

[0025] Step 4: Mix the solution after adjusting the pH in step 2 and the NaBF4 solution in step 3, and stir at a constant speed of 400 rpm / min for 1 hour;

[0026] Step 5: Transfer the solution in step 4 to a 100 mL polytetrafluoroethylene-lined reactor, seal it, heat it at 160°C for 5 h, and cool it naturally to room temperature;

[0027] Step 6: The precipitate in the above step 5 is separated by a centrifuge, and washed with deionized water and ethanol to remove impurities to obtain a final sample.

[0028] The preparation method of the above-mentioned photoluminescent low-haze surface treatment film, the mass parts of calcium nitrate, cerium nitrate, terbium nitrate, disodium ethylenediaminetetraacetic acid and deionized water in step one are: 1-5 mass parts, 0.1-0.5 mass parts, 0.1-0.5 mass parts, 0.2-0.6 mass parts and 30-60 mass parts respectively; in step three, the concentration of sodium fluoroborate (NaBF4) solution is 2-10, and the mass part is 0.2-1 mol / L.

[0029] In the method for preparing the above-mentioned photoluminescent low-haze surface treatment film, in the step c and the step d, the mass ratio of the two parts of SiO2 adsorption leveling agent added is 6:4-7:3.

[0030] The beneficial effects of the present invention are:

[0031] The present invention prepares Ce by hydrothermal synthesis method 3+ and Tb 3+ Co-doped CaF2 phosphors, oxides doped with rare earth nanocrystals can effectively improve visible light transmission, containing Ce 3+ and Tb 3+The nanoparticles absorb ultraviolet light and have little effect on the transmittance of visible light. At the same time, co-doping has the performance of energy transfer, which improves the photoluminescence performance. The UV laser can selectively highlight the image and eliminate unnecessary external reflections. Therefore, it can solve the problem of reflected light on the display panel surface and dim light spot of the laser pen in the display screen.

[0032] The SiO2 adsorption leveling agent is introduced into it, and the aggregation and dispersion of the phosphor particles in the coating liquid are controlled by controlling the addition amount and the order of addition. The coating liquid is applied to the hardened film, which not only makes it have high clarity and glossiness, but also has good anti-glare performance. The prepared low-haze surface treatment film will be widely used in display screens, breaking the monopoly of Korean and Japanese technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 3D microscope photo (50X) of the treated film prepared in Example 2 of the present invention;

[0034] Figure 2 3D microscope photo (50X) of the treated film prepared in Comparative Example 1;

[0035] Figure 3 3D microscope photo (50X) of the treated film prepared in Comparative Example 2;

[0036] Figure 4 This is a 3D microscope photograph (50X) of the treated film prepared in Comparative Example 3. DETAILED DESCRIPTION

[0037] The present invention prepares Ce by hydrothermal synthesis method 3+ and Tb 3+ The co-doped CaF2 phosphor, in which CaF2 particles are selected, is because CaF2 particles have good optical properties and physical stability. CaF2 particles have good light transmittance and do not affect the clarity of the display screen. CaF2 particles have high transmittance in the 0.13-11.3μm band, up to 95%, which enables them to effectively transmit light in a wide spectral range, and can transmit the luminescence of rare earth metals well, which is conducive to the realization of efficient optical applications; at the same time, the particle has a high refractive index, and when light propagates in the crystal, no additional optical path difference or polarization state change will be generated due to the birefringence phenomenon, which can ensure the quality and stability of the optical signal.

[0038] Since the CaF2 particle crystal belongs to the equiaxed crystal system, cubic crystal structure, and high symmetry, it is conducive to the uniform doping and distribution of rare earth metal particles in the crystal, and can provide suitable lattice sites for rare earth metal ions. In addition, the particle is very easy to prepare large-sized luminescent crystals, which meets the needs of large-sized optical components and reduces the preparation cost and process difficulty. When the particle is exposed to radiation, it has a strong resistance and is not prone to serious performance degradation or damage due to radiation. This is very beneficial for some application scenarios that may be in a radiation environment (such as the nuclear industry, etc.), and can ensure that the crystal can still work normally in harsh environments.

[0039] The present invention uses Ce 3+ and Tb 3+ Co-doping, Ce 3+ Can effectively transfer energy to Tb 3+ , Ce 3+ It has a high energy absorption capacity and its emission spectrum is similar to that of Tb 3+ The absorption spectra of Ce have good overlap, which allows energy to be transferred from Ce 3+ Transfer to Tb 3+ , thereby enhancing Tb 3+ Compared with the luminous intensity of Tb doped alone 3+ In comparison, Ce 3+ and Tb 3+ Co-doping can improve the overall luminescence intensity. 3+ To Tb 3+ The energy transfer process increases Tb 3+ The number of excited state layouts makes Tb 3+ It can generate more photons, thereby enhancing the luminous intensity of the material, and can better improve the problem of dim light spot when the laser pen is irradiated on the display screen.

[0040] In the present invention, Ce 3+ and Tb 3+ The co-doping ratio will also have many effects on the performance of the crystal. Different addition ratios will affect the energy transfer efficiency. 3+ The doping concentration is 0.2% to 0.5%, doped with 0.5% Ce 3+ The CaF2 main body has the best luminescence performance. At 475nm~535nm, Tb 3+ When the doping concentration is within the range of 1% to 3%, the luminescence performance increases with the Tb 3+ The doping concentration increases first and then decreases. When the concentration is 2%, the luminescence performance is the highest. 3+ The concentration of Tb 3+ Ion pair Ce 3+Ions have the function of energy transfer. The luminous intensity of CaF2 phosphor was studied. The best spectral conversion performance is CaF2: 0.5% Ce 3+ ~2% Tb 3+ Phosphor (0.5% Ce 3+ The optimal concentration is 2% for Tb 3+ optimal concentration).

[0041] In the present invention, Ce 3+ and Tb 3+ The particle size of the co-doped CaF2 phosphor is 500-700nm. Controlling the size of the phosphor particles is crucial to the formation of small particle aggregation. When the particle size is less than 500nm, the particles are too small to meet the anti-glare performance of the coating film. If the anti-glare performance is poor, the film will be shiny and cannot meet the visual requirements. If the particle size is greater than 700nm, when the SiO2 adsorption leveling agent is added, the particles will aggregate too much, resulting in an unstable coating liquid state and an increased particle sedimentation rate. At the same time, the film haze will be too high, the clarity will decrease, the gloss will decrease, and the anti-glare effect will be too strong, which cannot meet the requirements of the display panel. Therefore, the particle size needs to be controlled within the range of 500-700nm.

[0042] The leveling agent used in the present invention is a SiO2 adsorption leveling agent, which is usually made by using silicon dioxide as a carrier and adsorbing other functional components such as polyacrylate, silicone resin and fluorine surfactant. This type of leveling agent can eliminate surface defects such as orange peel, shrinkage cavities, pinholes, etc., and has the effect of leveling and gloss enhancement. It has the advantages of good leveling, low dosage and high gloss, and can also improve the smoothness and surface hardness of the coating. First, Ce 3+ and Tb 3+ The co-doped CaF2 phosphor nanoparticles are uniformly dispersed in the solvent, and then SiO2 adsorption leveling agent is added. The nanoparticles are adsorbed to the SiO2 surface through -OH, and then coated on the film surface to form a surface treatment film with small particle aggregation morphology (see Figure 1 ).

[0043] The SiO2 adsorption leveling agent described in the present invention is added twice. The purpose of the first addition is to improve the leveling effect of the film surface, improve the surface smoothness and coating liquid stability, and the purpose of the second addition is to form a small particle aggregation effect. 3+ and Tb 3+The addition ratio of the co-doped CaF2 phosphor and the SiO2 adsorbed leveling agent is 1:3%-8%. The amount of the leveling agent added directly affects the stability of the coating solution and the agglomeration effect formed. If the amount of the leveling agent added is insufficient, a complete and effective monolayer cannot be formed on the surface of the coating, and the surface tension of the coating cannot be fully reduced, which will cause poor leveling problems and affect the appearance flatness and glossiness of the coating film; if the amount of the leveling agent added is too much, sagging and dripping will occur, which will also affect the quality and appearance of the coating film. In the present invention, when the proportion of SiO2 adsorbed leveling agent is less than 0.1%, Ce in the coating solution 3+ and Tb 3+ The co-doped CaF2 phosphor nanocrystal particles cannot form a small particle aggregation state, and are monodispersed as a whole, and cannot form a certain anti-glare effect on the surface treatment film; however, if the proportion of SiO2 adsorbed leveling agent is greater than 0.5%, the apparent leveling of the low haze surface treatment film is poor and a uniform apparent coating effect cannot be formed.

[0044] In the present invention, the organic solvent is any one of isopropanol, ethyl acetate, and butyl acetate, or a mixture of any two thereof. The coating formed by the coating solution formed by such solvent has good surface leveling, less corrosiveness to the substrate, and less number of crystal points.

[0045] In the present invention, the transparent support can be a triacetyl cellulose film, a polyester film, a PMMA film, or a SRF film. Such films are important components of polarizers, and their thickness must be between 50 μm and 125 μm, wherein the coating thickness is 3 to 5 μm. If the coating thickness is too thin, it will affect the physical properties of the surface treatment film, such as low hardness and poor friction resistance; but if the thickness is too thick, it will have a great impact on the surface roughness, anti-glare performance, and clarity, so the coating thickness must be between 3 to 5 μm.

[0046] The preparation method of the photoluminescent low-haze surface treatment film of the present invention comprises: firstly synthesizing Ce by a typical hydrothermal method 3+ and Tb 3+ The co-doped CaF2 phosphor is added into the mixed solvent in a certain proportion and stirred by a high-speed stirrer to mix the synthesized Ce 3+ and Tb 3+The co-doped CaF2 phosphor is dispersed into single-particle nanoparticles, and a SiO2 adsorption leveling agent is added to the uniformly mixed single-particle nanoparticles. Subsequently, the resin is added to a solvent for dilution in a certain proportion, and a certain proportion of SiO2 adsorption leveling agent is added, and stirred at a low speed; finally, the nanoparticle pre-solution and the resin dilution are mixed, and a high-speed stirrer is used to stir to obtain the prepared coating liquid, and the coating liquid is scraped onto a transparent support through a wire rod, dried at 85°C, and then UV cured to obtain the photoluminescent low-haze surface treatment film.

[0047] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in combination with the embodiment of the present invention and the accompanying drawings. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meaning understood by people with general skills in the field to which the present invention belongs.

[0048] In the following examples, Ce 3+ and Tb 3+ The co-doped CaF2 phosphors were all synthesized by a typical hydrothermal method, with the following specific steps: Step 1: Calcium nitrate (Ca(NO3)2·6H2O), cerium nitrate (Ce(NO3)3·6H2O), terbium nitrate (Tb(NO3)3·5H2O) and disodium ethylenediaminetetraacetic acid (Na2EDTA) were dissolved in deionized water and stirred for 20 min using a high-speed stirrer at a speed of 1000 rpm / min;

[0049] Step 2: Use ammonia water to adjust the pH of the solution in step 1 to 6-7;

[0050] Step 3: dissolving sodium fluoroborate (NaBF4) to prepare a sodium fluoroborate (NaBF4) solution;

[0051] Step 4: Mix the solution after adjusting the pH in step 2 and the NaBF4 solution in step 3, and stir at a constant speed of 400 rpm / min for 1 hour;

[0052] Step 5: Transfer the solution in step 4 to a 100 mL polytetrafluoroethylene-lined reactor, seal it, heat it at 160°C for 5 h, and cool it naturally to room temperature;

[0053] Step 6: The precipitate in the above step 5 is separated by a centrifuge, and washed with deionized water and ethanol to remove impurities to obtain a final sample.

[0054] The mass fractions of calcium nitrate, cerium nitrate, terbium nitrate, disodium ethylenediaminetetraacetic acid and deionized water in the step one are 1 to 5 mass parts, 0.1 to 0.5 mass parts, 0.1 to 0.5 mass parts, 0.2 to 0.6 mass parts and 30 to 60 mass parts respectively; in the step three, the concentration of the sodium fluoroborate (NaBF4) solution is 2 to 10, and the mass fraction is 0.2 to 1 mol / L.

[0055] Example 1

[0056] Polyurethane acrylic resin 30g;

[0057] Isopropyl alcohol 33.2 g;

[0058] Butyl acetate 33.2 g;

[0059] SiO2 adsorption leveling agent 0.1g;

[0060] Photoinitiator 0.5g;

[0061] Ce 3+ and Tb 3+ 3g of co-doped CaF2 phosphor.

[0062] In a 100 mL beaker, add 23.2 g of isopropanol and butyl acetate, and weigh 3 g of Ce 3+ and Tb 3+ Co-doped CaF2 phosphor (the particle size of the phosphor is 589nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 98.8:0.2:1) and added into a beaker, stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min, and then 0.06 g of SiO2 adsorption leveling agent (BYK-350, Kunshan Daiquan Trading Co., Ltd.) was added and stirred for 20 minutes to obtain particle liquid A; 30 g of polyurethane acrylic resin (Sartomer CN9006NS) and 10 g of isopropanol and 10 g of butyl acetate were mixed, stirred at a low speed for 20 minutes at a speed of 500 rpm / min, and then 0.04 g of SiO2 adsorption leveling agent (BYK-352, Kunshan Daiquan Trading Co., Ltd.) was added and stirred for 20 minutes to obtain solution B; solution A was added into solution B, and 0.5 g of photoinitiator (TPO) was added and stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0063] The coating liquid was coated on the outer surface of a 50 μm thick optical grade polytriacetyl cellulose film (TAC film) roll with a wire rod, the coating thickness was 3.2 μm and dried at 85°C for 2 min, and the dried coating was cured under ultraviolet light (UV energy of ultraviolet light curing was 500 mJ / cm), and finally the desired surface treatment film was obtained. The hardness, wear resistance, glossiness, clarity and 3D microscope of the surface treatment film were tested.

[0064] Example 2

[0065] Polyurethane acrylic resin 35g;

[0066] Isopropyl alcohol 29.125 g;

[0067] Ethyl acetate 29.125 g;

[0068] SiO2 adsorption leveling agent 0.25g;

[0069] Photoinitiator 1.5g;

[0070] Ce 3+ and Tb 3+ 5g of co-doped CaF2 phosphor.

[0071] In a 100 mL beaker, add 19.125 g of isopropanol and ethyl acetate, and weigh 5 g of Ce 3+ and Tb 3+ Co-doped CaF2 phosphor (the particle size of the phosphor is 605nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 98.2:0.3:1.5) and added into a beaker, stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min, then 0.15 g of SiO2 adsorption leveling agent (Tech-9030, Tiger Additive) was added, and stirring was continued for 20 min to obtain particle liquid A; 35 g of polyurethane acrylic resin (EB8602, Allnex) and 10 g of isopropanol and 10 g of ethyl acetate were mixed, stirred at a low speed for 20 min at a speed of 500 rpm / min, then 0.1 g of SiO2 adsorption leveling agent (Tech-9043, Tiger Additive) was added and stirred for 20 min to obtain solution B; solution A was added into solution B, and 1.5 g of photoinitiator (TPO) was added and stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0072] The coating liquid was coated on the outside of the 80μm-SRF film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.6μm. The dried coating was cured under ultraviolet light (the UV energy of ultraviolet light curing was 500mJ / cm), and finally the desired surface treatment film was obtained. The hardness, wear resistance, glossiness and clarity of the surface treatment film were tested, as shown in Table 1 below. The 3D microscope of the treatment film was shown in Table 1 below. Figure 1 .

[0073] Example 3

[0074] Polyurethane acrylic resin 40g;

[0075] Isopropyl alcohol 24.8 g;

[0076] Ethyl acetate 24.8 g;

[0077] SiO2 adsorption leveling agent 0.4g;

[0078] Photoinitiator 3g;

[0079] Ce 3+ and Tb 3+ 7g of co-doped CaF2 phosphor.

[0080] In a 100 mL beaker, add 14.8 g of isopropanol and ethyl acetate, and weigh 7 g of Ce 3+ and Tb 3+ Co-doped CaF2 phosphor (the particle size of the phosphor is 650nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 97.8:0.4:1.8) and added into a beaker, stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min, then 0.28 g of SiO2 adsorption leveling agent (BYK-3751, BYK Chemical) was added, and stirring was continued for 20 min to obtain particle liquid A; 40 g of polyurethane acrylic resin (Agisyn 670A2, DSM) was mixed with 10 g of isopropanol and 10 parts by weight of ethyl acetate, stirred at a low speed for 20 min with a speed of 500 rpm / min, then 0.12 g of SiO2 adsorption leveling agent (BYK-3550, BYK Chemical) was added and stirred for 20 min to obtain solution B; solution A was added into solution B, and 3 g of photoinitiator (TPO) was added and stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0081] The coating liquid was coated on the outside of a 125 μm-PMMA film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.4 μm. The dried coating was cured under ultraviolet light (UV energy of ultraviolet light curing was 500 mJ / cm), and the desired surface treatment film was finally obtained. The hardness, wear resistance, glossiness, clarity and 3D microscope of the surface treatment film were tested.

[0082] Example 4

[0083] Polyurethane acrylic resin 40g;

[0084] Butyl acetate 23.25 g;

[0085] Ethyl acetate 23.25 g;

[0086] SiO2 adsorption leveling agent 0.5g;

[0087] Photoinitiator 5g;

[0088] Ce 3+ and Tb 3+ 8g of co-doped CaF2 phosphor.

[0089] In a 100 mL beaker, add 13.25 g of butyl acetate and ethyl acetate, and weigh 8 g of Ce 3+ and Tb 3+ Co-doped CaF2 phosphor (the particle size of the phosphor is 680nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 97.5:0.5:2) and added into a beaker, stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min, and then 0.35 g of SiO2 adsorption leveling agent (BYK-399, BYK Chemical) was added, and the stirring was continued for 20 minutes to obtain particle liquid A; polyurethane acrylic resin (Agisyn242, DSM) was mixed with 10 g of butyl acetate and 10 g of ethyl acetate, and stirred at a low speed for 20 minutes at a speed of 500 rpm / min, and then 0.15 g of SiO2 adsorption leveling agent (BYK-3560, BYK Chemical) was added and stirred for 20 minutes to obtain solution B; solution A was added into solution B, and 5 g of photoinitiator (TPO) was added and stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0090] The coating liquid was coated on the outside of a 125 μm PET polyester film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.8 μm. The dried coating was cured under ultraviolet light (UV energy of ultraviolet light curing was 500 mJ / cm), and the desired surface treatment film was finally obtained. The hardness, wear resistance, glossiness, clarity and 3D microscope of the surface treatment film were tested.

[0091] Comparative Example 1

[0092] Polyurethane acrylic resin 40g;

[0093] Butyl acetate 23.25 g;

[0094] Ethyl acetate 23.25 g;

[0095] SiO2 adsorption leveling agent 0.5g;

[0096] Photoinitiator 5g;

[0097] Ce 3+ and Tb 3+ 8g of co-doped CaF2 phosphor.

[0098] In a 100 mL beaker, add 13.25 g of butyl acetate and ethyl acetate, and weigh 8 g of Ce 3+ and Tb 3+ Co-doped CaF2 phosphor (the particle size of the phosphor is 680nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 97.5:0.5:2) and added into a beaker, stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min to obtain particle liquid A; 40g of polyurethane acrylic resin (Agisyn 242, DSM) and 10g of butyl acetate and 10g of ethyl acetate were mixed, stirred at a low speed for 20 minutes at a speed of 500 rpm / min to obtain solution B; solution A was added into solution B, and 5 parts by weight of photoinitiator (TPO), 0.35g of SiO2 adsorption leveling agent (BYK-399, BYK Chemical) and 0.15g of SiO2 adsorption leveling agent (BYK-3560, BYK Chemical) were added, and stirred for 20 minutes with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0099] The coating liquid was coated on the outside of a 125 μm PET polyester film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.3 μm. The dried coating was cured under ultraviolet light (the UV energy of ultraviolet light curing was 500 mJ / cm), and the desired surface treatment film was finally obtained. The hardness, wear resistance, glossiness, and clarity of the surface treatment film were tested, as shown in Table 1 below. The 3D microscope of the treatment film is shown in Table 1 below. Figure 2 .

[0100] Comparative Example 2

[0101] Polyurethane acrylic resin 40g;

[0102] Isopropyl alcohol 21.3 g;

[0103] Ethyl acetate 21.3 g;

[0104] SiO2 adsorption leveling agent 0.4g;

[0105] Photoinitiator 3g;

[0106] Ce 3+ and Tb 3+ 14g of co-doped CaF2 phosphor.

[0107] In a 100 mL beaker, add 11.3 g of isopropanol and ethyl acetate, and weigh 14 g of Ce 3+ and Tb 3 + Co-doped CaF2 phosphor (the particle size of the phosphor is 650nm, CaF2 and Ce 3+ and Tb 3+ The doping ratio is 97.8:0.4:1.8) and added into a beaker, stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min, then 0.28 g of SiO2 adsorption leveling agent (BYK-3751, BYK Chemical) was added, and stirring was continued for 20 min to obtain particle liquid A; 40 g of polyurethane acrylic resin (Agisyn 670A2, DSM) was mixed with 10 g of isopropanol and 10 g of ethyl acetate, stirred at a low speed for 20 min at a speed of 500 rpm / min, then 0.12 g of SiO2 adsorption leveling agent (BYK-3550, BYK Chemical) was added and stirred for 20 min to obtain solution B; solution A was added into solution B, and 3 g of photoinitiator (TPO) was added and stirred for 20 min with a high-speed stirrer at a speed of 1000 rpm / min to obtain a coating liquid.

[0108] The coating liquid was coated on the outside of the 125μm-PMMA film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.2μm. The dried coating was cured under ultraviolet light (UV energy of ultraviolet light curing was 500mJ / cm), and finally the desired surface treatment film was obtained. The hardness, wear resistance, glossiness and clarity of the surface treatment film were tested, as shown in Table 1 below, and the 3D microscope was used to test the hardness, wear resistance, glossiness and clarity of the surface treatment film ... Figure 3 .

[0109] Comparative Example 3

[0110] Polyurethane acrylic resin 35g;

[0111] Isopropyl alcohol 29.125 g;

[0112] Ethyl acetate 29.125 g;

[0113] SiO2 adsorption leveling agent 0.25g;

[0114] Photoinitiator 1.5g;

[0115] 5g carbon quantum dot phosphor.

[0116] In a 100mL beaker, 19.125g of isopropanol and ethyl acetate were added respectively, and the weighed carbon quantum dot phosphor (the particle size of the phosphor is 20nm) was added to the beaker, and stirred for 20min with a high-speed stirrer at a speed of 1000rpm / min. Subsequently, 0.15g of SiO2 adsorption leveling agent (Tech-9030, Tiger Additive) was added, and stirring was continued for 20min to obtain particle liquid A; 35g of polyurethane acrylic resin (EB8602, Allnex) and 10g of isopropanol and 10g of ethyl acetate were mixed, and stirred at a low speed for 20min at a speed of 500rpm / min, and then 0.1g of SiO2 adsorption leveling agent (Tech-9043, Tiger Additive) was added and stirred for 20min to obtain solution B; solution A was added to solution B, and 1.5g of photoinitiator (TPO) was added and stirred for 20min with a high-speed stirrer at a speed of 1000rpm / min to obtain a coating liquid.

[0117] The coating liquid was coated on the outside of the 80μm-SRF film roll with a wire rod and dried at 85°C for 2 minutes. The coating thickness was 3.5μm. The dried coating was cured under ultraviolet light (the UV energy of ultraviolet light curing was 500mJ / cm), and the desired surface treatment film was finally obtained. The hardness, wear resistance, glossiness and clarity of the surface treatment film were tested, as shown in Table 1, and the 3D microscope was used to test the hardness, wear resistance, glossiness and clarity of the surface treatment film, as shown in Table 1. Figure 4 .

[0118] The performance test methods are as follows:

[0119] (1): Coating pencil hardness test

[0120] Coating hardness tester (Shanghai Pushen Chemical Machinery Co., Ltd.; model: BY), load 500g.

[0121] (2): Coating scratch resistance (wear resistance)

[0122] The scratch resistance of the anti-glare layer was measured according to the method specified in HG / T 4303. The load was 1000g and the friction was repeated 100 times. No scratches were recorded as "○", 1 to 10 scratches were recorded as "△", and more than 10 scratches were recorded as "×".

[0123] (3): Adhesion test

[0124] Use a scribing knife to draw 11 scratches in mutually perpendicular directions on the hardened film sample to obtain 100 small grids of uniform size. Use 3M tape (Scotch transparent tape) to quickly stick the hardened film sample (repeat 3 times), observe whether the hardened film sample falls off within the 100 grids, and record the values.

[0125] (4): Observation

[0126] Select 3-5 people in the industry to observe the texture (crystal points, silk rod marks, clarity) of the hardened film samples with the naked eye. Good appearance, no crystal points, and silk rod marks are recorded as "○", good appearance, and many crystal points are recorded as "△", and poor apparent clarity and many crystal points are recorded as "×".

[0127] (5): Clarity, haze, glossiness, transmittance

[0128] The data is obtained by testing using a clarity meter, a gloss meter, and a haze meter.

[0129] The test results are shown in Table 1:

[0130] Table 1 Test results of various properties of surface treatment film samples

[0131] Samples hardness Wear-resistant Adhesion Clarity Appearance Glossiness Haze Light transmittance Example 1 3H △ 100% 92.13 ○ 158 3.28 91.23 Example 2 3H △ 100% 91.86 ○ 158 3.33 91.41 Example 3 3H △ 100% 91.89 ○ 161 3.32 91.35 Example 4 3H △ 100% 91.55 ○ 165 3.54 91.46 Comparative Example 1 3H △ 100% 91.95 △ 159 3.68 91.28 Comparative Example 2 3H △ 100% 88.64 △ 154 5.78 90.12 Comparative Example 3 2H × 100% 91.96 ○ 156 2.35 91.58

[0132] From Table 1, it can be seen that Examples 1-4 can meet the requirements of customers and manufacturers in terms of hardness, wear resistance, adhesion, clarity, gloss, haze, and light transmittance. Figure 1 This is the particle aggregation morphology required for the low haze surface treatment film, that is, the particles in the film have both a dispersed state and a small particle aggregation state. Only this state can be used in the polarizer market. Compared with Example 4, the addition method of the SiO2 adsorption leveling agent in Comparative Example 1 is incorrect. The preparation method of Comparative Example 1 will form Figure 2The particle morphology of this morphology is that all particles are evenly dispersed, and there are many crystal points (point defects) on the surface of the treated film, which cannot be used in the polarizer market; Compared with Example 3, the Ce 3+ and Tb 3+ If the amount of co-doped CaF2 phosphor added is too much, the haze of the film will be high and the clarity will be reduced. The haze of the film used in the polarizer market needs to be between 3-4 and the clarity needs to be above 90°. In addition, the film coated by the coating liquid has too many particles and its aggregation form is too large. There are no monodispersed particles and there are many crystal points on the surface of the treated film. Therefore, it cannot be used as a polarizer protective film. Compared with Example 2, Comparative Example 3 selects carbon quantum dot phosphor. The nanoparticle size of the phosphor is smaller, and the particles cannot be fully displayed on the coating surface, resulting in low haze of the low haze surface treated film, poor anti-glare properties, and weak particle aggregation ( Figure 4 ), at the same time, its hardness and friction resistance are relatively weak, and its physical properties are difficult to meet market demand.

[0133] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A photoluminescent low-haze surface treatment film, characterized in that: The treatment film includes a transparent support and a hardened coating layer coated on the surface of the transparent support, wherein the hardened coating layer is formed by coating a coating liquid on the surface of the transparent support, drying in an oven, and curing with ultraviolet light, wherein one hundred parts of the coating liquid include the following materials: 30-40 parts of polyurethane acrylic resin; 46.5-66.4 parts of organic solvent; SiO2 adsorption leveling agent 0.1-0.5 parts; 0.5-5 parts of photoinitiator; Ce 3+ and Tb 3+ 3 to 8 parts of co-doped CaF2 phosphor.

2. The photoluminescent low-haze surface treatment film according to claim 1, characterized in that: The Ce 3+ and Tb 3+ The particle size of the co-doped CaF2 phosphor is 500~700nm.

3. The photoluminescent low-haze surface treatment film according to claim 1, characterized in that: The SiO2 adsorption leveling agent is any one of polyacrylate, silicone resin and fluorine surfactant.

4. The photoluminescent low-haze surface treatment film according to claim 1, characterized in that: The Ce 3+ and Tb 3+ The mass ratio of the co-doped CaF2 phosphor to the SiO2 adsorbed leveling agent is 1:(0.03~0.08).

5. The photoluminescent low-haze surface treatment film according to claim 1, characterized in that: The organic solvent is any one of isopropanol, ethyl acetate and butyl acetate or a mixture of any two of them; the photoinitiator is TPO.

6. The photoluminescent low-haze surface treatment film according to claim 1, characterized in that: The transparent support is a triacetyl cellulose film, a polyester film, a PMMA film, or a SRF film, and has a thickness of 50 μm to 125 μm, wherein the coating thickness is 3 to 5 μm.

7. A method for preparing a photoluminescent low-haze surface treatment film according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: a. Preparation of Ce by hydrothermal synthesis 3+ and Tb 3+ Co-doped CaF2 phosphor; b. Prepare Ce 3+ and Tb 3+ The co-doped CaF2 phosphor is added to a certain amount of solvent and dispersed into single-particle nanoparticles by high-speed stirring; c. Adding part of SiO2 adsorbing leveling agent to the uniformly mixed single-particle nanoparticles to obtain nanoparticle pre-solution A; d. Mix and dilute the formulated amount of polyurethane acrylic resin with a certain amount of solvent, add another part of SiO2 adsorption leveling agent after mixing, and stir at a low speed to obtain resin dilution B; e. Add the nanoparticle pre-solution A to the resin diluent B, and add a formulated amount of photoinitiator, and stir at high speed to obtain a coating solution; f. The coating liquid is coated onto a transparent support by a wire rod, dried at 85° C., and then UV cured to obtain the photoluminescent low-haze surface treatment film.

8. The method for preparing the photoluminescent low-haze surface treatment film according to claim 7, characterized in that: In the step a, Ce is prepared by hydrothermal synthesis 3+ and Tb 3+ The co-doped CaF2 phosphor includes the following steps: Step 1: Dissolve calcium nitrate (Ca(NO3)2·6H2O), cerium nitrate (Ce(NO3)3·6H2O), terbium nitrate (Tb(NO3)3·5H2O) and disodium ethylenediaminetetraacetic acid (Na2EDTA) in deionized water and stir for 20 min using a high-speed stirrer at a speed of 1000 rpm / min; Step 2: Use ammonia water to adjust the pH of the solution in step 1 to 6-7; Step 3: dissolving sodium fluoroborate (NaBF4) to prepare a sodium fluoroborate (NaBF4) solution; Step 4: Mix the solution after adjusting the pH in step 2 and the NaBF4 solution in step 3, and stir at a constant speed of 400 rpm / min for 1 hour; Step 5: Transfer the solution in step 4 to a 100 mL polytetrafluoroethylene-lined reactor, seal it, heat it at 160 °C for 5 h, and cool it naturally to room temperature; Step 6: The precipitate in the above step 5 is separated by a centrifuge, and washed with deionized water and ethanol to remove impurities to obtain a final sample.

9. The method for preparing a photoluminescent low-haze surface treatment film according to claim 8, characterized in that: The mass fractions of calcium nitrate, cerium nitrate, terbium nitrate, disodium ethylenediaminetetraacetic acid and deionized water in the step one are 1 to 5 mass parts, 0.1 to 0.5 mass parts, 0.1 to 0.5 mass parts, 0.2 to 0.6 mass parts and 30 to 60 mass parts respectively; in the step three, the concentration of the sodium fluoroborate (NaBF4) solution is 2 to 10, and the mass fraction is 0.2 to 1 mol / L.

10. The method for preparing a photoluminescent low-haze surface treatment film according to claim 7, characterized in that: In the step c and step d, the mass ratio of the two parts of SiO2 adsorption leveling agent added is 6:4-7:3.